Combined effects of growth hormone and testosterone replacement treatment in heart failure - Salzano, Andrea (ESC Heart Fail, 2019)
AIMS: Although preliminary studies have demonstrated safety and effectiveness of single replacement therapy for growth hormone deficiency or testosterone deficiency in heart failure (HF), no data are available regarding the combined treatment with both GH and T in this setting. Thus, the aim of the present hypothesis generating pilot study was to evaluate the effectiveness and safety of multiple hormonal replacement therapies in chronic HF. METHODS AND RESULTS: Five stable HF with reduced ejection fraction patients, with a concomitant diagnosis of growth hormone deficiency and testosterone deficiency, on top of guideline‐based HF treatment underwent 1 year of GH replacement therapy by subcutaneous injections of somatotropin at a dose of 0.012 mg/kg every second day. After 12 months, a T replacement treatment was added at a dosage of 1000 mg every 3 months. Each patient underwent a complete M‐mode, two‐dimensional, and Doppler echocardiographic examination, and an incremental symptom‐limited cardiopulmonary exercise test on a bicycle ergometer at baseline (BL), after 1 year of GH treatment (V1), and after 1 year of combined GH + T treatments (V2). One‐year of GH treatment resulted in a significant improvement in left ventricular ejection fraction (+5.4%, P < 0.01), New York Heart Association functional class (P < 0.05), and peak oxygen consumption (VO(2) peak) (+19.3%, P < 0.01), and in a significant reduction in NT‐proBNP levels (−35.1%, P < 0.01). Notably, one additional year of combined GH and T replacement therapy induced a further increase in VO(2) peak (+27.7%, final delta change + 52.44%, P < 0.01), as well as a significant improvement in muscular strength, as assessed by handgrip dynamometry (+17.5%, final delta change + 25.8%, P < 0.01). These beneficial effects were paralleled with an improvement of the overall clinical status (as assessed by New York Heart Association class). Of note, neither adverse effects nor cardiovascular events were reported during the follow‐up period. CONCLUSIONS: Our preliminary data suggest for the first time that combined replacement therapy with GH and T could be considered safe and therapeutic in HF patients with multiple hormone deficiencies, supporting the hypothesis that multiple hormone deficiencies syndrome can be considered as a novel and promising therapeutic target in HF. Further studies with a more robust design and larger population are needed.